INSTRUMENTS FOR IMPLEMENTING E-JUSTICE: EXPERIENCE OF THE REPUBLIC OF POLAND AND ITALY (Bulletin of criminological association of Ukraine, 2024)
The article studies the experiences of the Republic of Poland and Italy in implementing electronic justice. The paper substantiates the relevance of introducing innovative mechanisms in judicial proceedings in the context of the digitalization of society. The article determines that electronic justice can increase the efficiency, transparency, accessibility, and promptness of the judicial system. The paper analyzes Polish e-judiciary tools: remote case consideration, digital recording of proceedings, electronic document delivery to lawyers through the e-Service, and the functioning of electronic courts with automated proceedings. The paper examines Italian PCT system for electronic civil proceedings with the use of certified mail, electronic signatures, and cloud technologies. The presented statistical data indicate the successful integration of e-tools into the judicial systems of both countries and the budget savings from their implementation and use. The paper identifies the advantages of e-justice: increased efficiency, accessibility, transparency of judicial proceedings, and resource savings. The author outlines the areas for borrowing the positive experience of Poland and Italy to improve the Ukrainian model of e-justice, taking into account its specifics. The author emphasizes the importance of scientific substantiation of the introduction of electronic technologies into the judicial system as part of modernization aimed at increasing its efficiency and compliance with European standards.
Keywords: Republic of Poland; Italy; judiciary; electronic justice; e-Service; PST; SPID